The regional pattern of the US house price bubble: An application of SPC to city level data - Julia Freese (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2013)
The recent U.S. house price bubble and the subsequent deep financial crisis have renewed the interest in reliable identification methods for asset price bubbles. While there is a growing number of studies focussing on the detection of U.S. regional bubbles, estimations of the likely starting points in different local U.S. markets are still rare. Using regional data from 1990 to 2010 methods of Statistical Process Control (SPC) are used to test for house price bubbles in 17 major U.S. cities. Based on the EWMA control chart we also present estimations of the likely starting point of the regional bubbles. As a result, we find indications of house price bubbles in all 17 considered cities. Interestingly enough, the recent bubble was not a homogeneous event since regional starting points range from 1996 to 2002.
Keywords: C32; E44; R11; 330; statistical process control; real estate; bubble; regional U.S. house prices